2009
DOI: 10.1097/prs.0b013e3181adce61
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies Investigating the Effect of Subcutaneous Phosphatidylcholine Injections in the 3T3-L1 Adipocyte Model: Lipolysis or Lipid Dissolution?

Abstract: These results suggest that no enzymatic lipolytic pathway is induced. The decrease in volume after Lipostabil injections is likely attributable to the detergent effect of deoxycholate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 11 publications
1
42
0
3
Order By: Relevance
“…These findings suggest that deoxycholate is the primary active ingredient which plays a pivotal role in reduction of adipose tissue. A recent study using an in vitro model demonstrated DOC ability to reduce cell viability as in commercial formulas, not affecting the enzymatic lipolytic pathway (15). Isolated DOC ability to cause adipocyte lysis similar to commercial mixtures has been reported by an observational study on lipomas, showing that a volume reduction was possible using DOC injection alone; in addition, an acute inflammatory response, focal necrosis and haemorrhagic histology could be observed in this area (16).…”
mentioning
confidence: 84%
“…These findings suggest that deoxycholate is the primary active ingredient which plays a pivotal role in reduction of adipose tissue. A recent study using an in vitro model demonstrated DOC ability to reduce cell viability as in commercial formulas, not affecting the enzymatic lipolytic pathway (15). Isolated DOC ability to cause adipocyte lysis similar to commercial mixtures has been reported by an observational study on lipomas, showing that a volume reduction was possible using DOC injection alone; in addition, an acute inflammatory response, focal necrosis and haemorrhagic histology could be observed in this area (16).…”
mentioning
confidence: 84%
“…These results suggest that a PPC formulation without SD is sufficient to decompose fat cells. However, Klein et al [22] reported that neither isolated PPC nor deoxycholate induced lipolytic pathways. This discrepancy may reflect differences in the experimental ­conditions and/or the composition of the PPC formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct evidence is lacking. Bile acid deoxycholate has no pro-lipolytic activity in 3T3L-1 adipocytes (Klein et al, 2009). Therefore, further studies are needed to decipher the pro-lipolytic effects of bile acids.…”
Section: Bile Acidsmentioning
confidence: 99%